CONDITION OF THE ALVEOLAR BONE AND GINGIVAL TISSUE IN FEMALE RATS UNDER CONDITIONS OF UNBALANCED DIETS - Погребняк, Г.В. (World of Medicine and Biology, 2015)
The paper presents the results of research on alveolar bone and gingival tissue in female rats which were kept on the unbalanced feed rations on the levels of triglycerides in the tissues and resorption of alveolar bone. The levels of triglycerides in periodontal tissues from experimental animals depends on rations of feeding. An unbalanced diet feeding on the contents of high carbohydrate leads to increased levels of triglycerides, as a sign of insulin resistance, alveolar bone and gingival tissue. Alveolar bone resorption was estimated from the mean intensity to intense. When the content of animals on unbalanced on the fat of plant origin the diet of feeding some of the signs of insulin resistance in periodontal tissues and resorption of alveolar bone significantly enhanced. The feeding diet, unbalanced in content fat of animal origin does not affect the examined tissue.